1995
DOI: 10.1099/13500872-141-3-561
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pectin methylesterase and polygalacturonate lyase activity during differentiation of infection structures in Uromyces viciae-fabae

Abstract: The broad bean rust fungus Uromyces viciae-fabae differentiates infection structures up to the haustorial mother cell stage on thigmotropically inductive membranes in the absence of its host plant. Formation of pectin methylesterase (PME) and polygalacturonate lyase (PL), potentially involved in host cell wall degradation, was studied during infection structure differentiation by this biotrophic fungus. PME was first detectable when substomatal vesicles were formed and reached a maximum when infection hyphae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Cellulase production occurs already during appressorium formation. Pectin methylesterases are secreted during hypha development, and polygalacturonate lyase is produced during differentiation of haustorial mother cells (Heiler et al, 1993;Deising et al, 1995). In our study, we also found that in the M. larici-populina and poplar cultivars interaction, the peak value of ΔPMG appeared in 1 dpi and 5 dpi both in susceptible and resistant cultivars.…”
Section: Discussionsupporting
confidence: 70%
“…Cellulase production occurs already during appressorium formation. Pectin methylesterases are secreted during hypha development, and polygalacturonate lyase is produced during differentiation of haustorial mother cells (Heiler et al, 1993;Deising et al, 1995). In our study, we also found that in the M. larici-populina and poplar cultivars interaction, the peak value of ΔPMG appeared in 1 dpi and 5 dpi both in susceptible and resistant cultivars.…”
Section: Discussionsupporting
confidence: 70%
“…The dikaryotic urediospores of U. viciae-fabae secrete a number of cell-wall-degrading enzymes in a highly regulated manner. Cellulase production occurs already during appressorium formation (Heiler et al 1993), pectinmethylesterases are secreted during infection hypha development, and polygalacturonate lyase is produced during differentiation of haustorial mother cells (Deising et al 1995). Thus, the fungus seems to be adapted to the specific infection conditions found during stomatal penetration and subsequent host cell penetration.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that although turgor pressure may support penetration, enzymes seem to play a major role. However, since Uromyces is a biotrophic pathogen fed by haustoria that the fungus produces within living plant cells, enzyme secretion should be very restricted during the penetration process (Deising et al 1995). Therefore, this study was undertaken to investigate if and how far the wall at the penetration site of Uromyces vignae Barclay shows signs of enzymatic degradation.…”
mentioning
confidence: 99%
“…A study examining the pectin-degrading enzymes for obligate or biotrophic pathogens such as bean rust fungus Uromyces viciae-fabae 8 , lettuce downy mildew pathogen Bremia lactucae 48 , wheat powdery mildew fungus Blumeria graminis f. sp. tritici 43 , and apple scab fungus Venturia inaequalis 47 , has also been initiated.…”
Section: Introductionmentioning
confidence: 99%